Measuring synchronicity and co-movement of business cycles with an application to the euro area - Mark Mink; Jan P.A.M. Jacobs; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2007)
We develop multivariate measures of synchronicity and co-movement of business cycles. In addition to synchronicity, the co-movement measure takes differences between cycle amplitudes into account that have been overlooked in most previous studies. We apply the new measures to the euro area. Synchronicity and co-movement for the region as a whole do not exhibit a clear upward tendency. Although several countries saw the similarity of their business cycle vis-`a-vis the euro area reference cycle increase, national business cycles remain fairly diverse. Changes in business cycle amplitudes cause most of the observed change in cycle co-movement.
Keywords: E32; F02; F42; 330; business cycles; synchronisation; concordance; co-movement; cycle amplitudes; euro area; Konjunkturzusammenhang; Europäische Wirtschafts- und Währungsunion; Multivariate Analyse; EU-Staaten